Pengaruh Faktor Air Semen (FAS) Terhadap Toughness Beton - Armin Naibaho - (Jurnal Ilmiah Poli Rekayasa, 2017)
The pupose of this research is to observe the effect of water cement factors to the toughness of concrete :“How is the effect of water cement factors to the toughness of concrete?” Laboratory testing is done for concrete base material, that is aggregate: Rough (pebble), fine aggregate (sand), cement (PC= Portland Cement), water. The test object is in the form of a cylinder with mix design that have variation at water cement factors (cement water factors 0,35, cement water factors 0,40, and cement water factors 0,45) for 10 pieces, which is soaked for 26 days. On the 28th day, the object will be tested press.Based on analysis and discussion, then obtained that (1) From the mixed composistion based on Water Cement Factors, it is seen that the mixture using the lowest water cement factors, Cement Water Factors 0.35 will give a stronger press value and larger elastic modulus, 23,36 MPa at Cement Water Factors 0.40 (11,34%) and increased to 26,68 Mpa at Cement Water Factors 0.35 (27,17%). (2) Compared to the lowest Cement Water Factors, Cement Water Factors 0.35 will give a higher Work of Fracture ( Gf ). This is shown from Work of Fracture ( Gf ) to Cement Water Factors 0.45 = 31,445 N/m, increased to 34,582 N/m at Cement Water Factors 0.40 (9,025%) and increased to 35,582 N/m at Cement Water Factors 0.35 (13,156%). (3). Quantitatively the hardness, the bigger value of power achieved will show the bigger concrete ductile. This is shown from Stress Intensity Factor (K) to Cement Water Factors 0.45 = 0,8267 N/m, incresed to 0,8664 N/m at Cement Water Factors 0.40 (4,80%) and increased to 0,9088 N/m at Cement Water Factors 0.35 (9,93%).